2017
DOI: 10.3390/molecules22101773
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nanoemulsifying Drug Delivery Systems Containing Plantago lanceolata—An Assessment of Their Antioxidant and Antiinflammatory Effects

Abstract: The most important components of Plantago lanceolata L. leaves are catalpol, aucubin, and acteoside (=verbascoside). These bioactive compounds possess different pharmacological effects: anti-inflammatory, antioxidant, antineoplastic, and hepatoprotective. The aim of this study was to protect Plantago lanceolata extract from hydrolysis and to improve its antioxidant effect using self-nano-emulsifying drug delivery systems (SNEDDS). Eight SNEDDS compositions were prepared, and their physical properties, in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…The size meets the nano criteria and approaches the DNA size of about 10 nm [20]. The range of particle sizes in the study of SNEDDS formulations containing P. lanceolata was between 141,51 and 374,89 [19], while in the study of SNEDDS A, compactum, particle size was 13,97 [18]. The average droplet size of tetrandine SNEDDS was 19.75 nm.…”
Section: Characterizations Of Snedds Of Extract Singawalang Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The size meets the nano criteria and approaches the DNA size of about 10 nm [20]. The range of particle sizes in the study of SNEDDS formulations containing P. lanceolata was between 141,51 and 374,89 [19], while in the study of SNEDDS A, compactum, particle size was 13,97 [18]. The average droplet size of tetrandine SNEDDS was 19.75 nm.…”
Section: Characterizations Of Snedds Of Extract Singawalang Leavesmentioning
confidence: 99%
“…The selected SNEDDS formulation was stable for 6 months at room temperature. Another study stated that SNEDDS of Plantago lanceolata was stable for 1 month at room temperature [19].…”
Section: Characterizations Of Snedds Of Extract Singawalang Leavesmentioning
confidence: 99%
“…In addition, these formulations could efficiently deliver the black seed oil to the patient [ 337 ]. Many other studies showed the potential of SEDDSs in the oral delivery of herbal drugs, including [ 338 , 339 , 340 , 341 , 342 , 343 , 344 ].…”
Section: Advancements In Sneddssmentioning
confidence: 99%
“…The excipients contained in the SNEDDS tend to facilitate bioavailability of the drugs not merely by improving drug solubility and permeability but by circumventing the metabolism by liver microsomes and inhibiting P-gp efflux, along with the ability to facilitate lymphatic drug absorption. Several literature studies on various self-emulsifying formulations have reported potential improvement in the bioavailability of various drugs (Kalantari et al, 2017;Alhasani et al, 2019;Patki et al, 2019;Alsk€ ar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%